Habilidades sociais parentais e infantis, problemas de comportamento em pré-escolares: avaliação de pais e professores - Brasil, Silvany Ellen Risuenho (Universidade Federal de São Carlos, 2014)
Whereas the primary socialization of children happens within the family, where parents provide arrangements of reinforcement contingencies or offer models of behavior, including expanding and improving social skills classes. Childhood is considered a turning point for learning social skills, which are different classes of social behaviors present in the repertoire of an individual that promote a healthy and productive relationship with other people. Among the social skills, has the set of social skills specifically parental applicable to educational practices of their children, which is called parenting educative social skills (HSE-P). Many Brazilian studies have associated child behavior problems at HSE-P. Thus, this study aimed (a) establish and analyze the relationships between the parenting educative social skills repertoires, social skills of children and the occurrence of behavior problems of children; (b) compare the social skills and behavior problems of children, between the group of children whose parents have higher and lower educational repertoire of social skills and (c) compare the parenting educative social skills repertoire and the social skills repertoire of children between the group of children with more and less behavioral problems. Participated in the study 35 mothers and five fathers, with a mean age of 29 years (ranging from 19 to 66 years) of 40 children. These parents were responsible for 24 boys and 16 girls, aged between two and six years, attending public preschools in four cities in two states. Also responded to questionnaires 37 teachers, three male and 34 female. These teachers had, on average, 35 years of age ranging between 28 and 52 years. All had been teaching in regular class from kindergarten. To achieve the goals, have been applied the instruments Social Skills Rating System (SSRS) - version for parents and version for teachers and the Inventory of Social Educational Skills - IHSE-Del Prette, rather in the institution where the child studied or where participants indicated. Data were analyzed according to the standards of respective instruments. To establish relationships between variables Pearson's correlation test was used. The results indicated that parents had a higher frequency of HSE- P related to set boundaries, correct, control. The evaluation of the parents, the children were within the reference sample average for Social Skills and above average for Hyperactive behavior problems. According to the evaluation of teachers, these children were below average for Social Skills of Self-Control and Social Skills totals, and above average for problems of externalizing and internalizing behaviors. Significant positive correlations between HSE-P and social skills and academic performance of children, and significant and negative correlations between HSE-P and the problems of child behavior were found. As for comparative data, the group of children with parents with better repertoire of HSE-P showed better social skills related to Kindness, Assertiveness, Self / Civility, Passive Self and Self Defense. Children with higher levels of behavioral problems had lower social skills repertoire of Kindness, Self / Civility, Passive Self, Responsibility / Cooperation, Self-Control and Cooperation with peers. Overall, these data indicate that the better the repertoire of HSE-P, better social skills of children and lower the occurrence of behavior problems. So, intervention with parents with the goal of instrumentalize them can become a mechanism of protection effective to act in the primary prevention of child behavior problem, preventing these children are the target audience of Special Education since Childhood Education.
Keywords: Educação infantil; Habilidades sociais educativas; Problemas de comportamento; Special education; Childhood education; Parental educative social skills; Behavior problem; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL